Enhancing Tax Collection Efficiency in CIS Countries: Challenges, Reforms, and Strategic Imperatives - Berdieva Uguloy Abdurakhmonovna (Scientific Trends, 2025)
This article explores the dynamics of tax collection in the Commonwealth of Independent States (CIS), focusing on institutional development, policy reforms, and digital transformation. Drawing on cross-country comparisons and empirical data from 2010 to 2023, the study identifies persistent challenges such as informal economic activity, administrative inefficiencies, and low tax morale. It critically evaluates recent innovations in tax systems, particularly the role of digital tools in enhancing tax compliance. The article offers policy recommendations to strengthen fiscal capacity and build resilient tax administrations across the CIS.
Keywords: Tax administration, CIS, revenue mobilization, digital taxation, informal economy, fiscal reform, post-Soviet economies.